Biodiversity in the Rhizosphere of Selected Winter Wheat (Triticum aestivum L.) Cultivars—Genetic and Catabolic Fingerprinting - Agnieszka Wolińska; Agnieszka Kuźniar; Anna Gałązka (Agronomy, 2020)
The main goal of the study was to determine the biodiversity of bacteria and their metabolic profile in the rhizosphere of four winter wheat (Triticum aestivum L.) varieties (Hondia, Nordkap, Rotax, Tytanika) cultivated in Haplic Podzol soil in a no-tillage system. Two techniques, i.e., next generation sequencing (NGS, meta-barcoding of 16S rRNA community) and community level physiological profiling (CLPP), were applied to obtain a holistic picture of biodiversity. The basic soil chemical parameters (acidity, redox potential, carbon content, forms of nitrogen, and phosphorus) were also determined. It was found that the rhizospheric microbiome (at the genus level) of cv. Hondia and Rotax were significantly different from that present in the other cultivars studied. The CLPP technique demonstrated that microbial metabolic activity depended on both the type of substrate and wheat cultivars. Carbohydrates and carboxylic acids were the most easily utilized compounds in all rhizospheric soils. The principal component analysis (PCA) evidenced that the rhizospheric soils of Rotax and Nordkap were characterized by a higher functional activity (strong correlation with the Shannon-Wiener index, the Richness index, and utilization of hydrocarbons) than those of Hondia and Tytanika.